“QUALITY ASSURANCE AND ACCREDITATION OF FORENSIC SCIENCE LABORATORIES”: A PROGRAM FOR TRAINING QUALITY ASSURANCE MANAGERS - S. Kuz'min (Теория и практика судебной экспертизы, 2016)
The paper presents an overview of the innovational program of the continuing education course “Quality assurance and accreditation of forensic science laboratories” developed by the Department of Forensic Operations of the Institute of Law, Peoples' Friendship University of Russia. The course is designed to provide continuing education for forensic science organization employees responsible for quality control (quality assurance managers).